2003
DOI: 10.1097/01.mlr.0000076053.28108.f2
|View full text |Cite
|
Sign up to set email alerts
|

Rural-Urban Differences in Usual Source of Care and Ambulatory Service Use

Abstract: Results suggest that using rural and urban definitions that go beyond the traditional dichotomy of metropolitan and non-metropolitan may assist policymakers and researchers in identifying types of places where there is a disparity in access and subsequent utilization of health care. Rural residents, defined as totally rural in the urban influence coding scheme, may report having a health care provider but report fewer visits to health care providers during a year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 19 publications
3
110
1
Order By: Relevance
“…The authors concluded that a non-dichotomous definition may reveal hidden variation. 46 Hawley used both RUCCs and UICs to describe the variation in colon cancer incidence and mortality rates in Texas and concluded that finer delineations on the rural end of the scales revealed heterogeneity in rates with respect to African-Americans. 47 Similarly, we found much lower rates of mammography-detected breast cancer in North Carolina (NC) in the most rural areas using the UIC taxonomy; these differences would have been attenuated had we used a dichotomous measure.…”
Section: Us Census Urban and Ruralmentioning
confidence: 99%
“…The authors concluded that a non-dichotomous definition may reveal hidden variation. 46 Hawley used both RUCCs and UICs to describe the variation in colon cancer incidence and mortality rates in Texas and concluded that finer delineations on the rural end of the scales revealed heterogeneity in rates with respect to African-Americans. 47 Similarly, we found much lower rates of mammography-detected breast cancer in North Carolina (NC) in the most rural areas using the UIC taxonomy; these differences would have been attenuated had we used a dichotomous measure.…”
Section: Us Census Urban and Ruralmentioning
confidence: 99%
“…80 While many rural residents report having a health care provider, they tend to report fewer annual visits to health care providers than do residents of large metropolitan areas. 81 Within an urban environment, geography can influence the likelihood of health care use. In New York City, the overall revascularization rates among patients hospitalized with MI were higher in an affluent community than in two socioeconomically disadvantaged communities.…”
Section: Barriers To Accessmentioning
confidence: 99%
“…Demographic characteristics included race/ethnicity (white, African American, or Latina), age (<45, 45-49, 50-54, 55-59, or 60-64 years), marital status (married, widowed, divorced/separated, or never married) and area of residence. The urban/rural continuum of a woman's residence was determined by ZIP code/county of subject residence using the Urban Influence Coding scheme (Larson & Fleishman 2003). This measure is a 10-level summary variable with the value 0 representing the most urban areas and the value 9 representing the most rural areas.…”
Section: Dependent Variables: Intermediate Outcomes Of Diabetes Carementioning
confidence: 99%